Catamenial anaphylaxis: a woman under monthly progesterone curse. (4th January 2018) - Lin, Kyawzaw; Rasheed, Ameer; Lin, Sithu; Gerolemou, Louis
Abstract : Catamenial or cyclical anaphylaxis is a complex clinical syndrome with poorly reported incidence and prevalence in the literature review. The underlying mechanism is still a myth although a few proposed hypotheses are stated. Early recognition of these symptoms will bring optimal treatment and prevent unnecessary intubation and complications. Here, we present a 48-year-old woman without significant medical and family history with recurrent angioedema in the setting of catamenial anaphylaxis or cyclical anaphylaxis in the setting of progesterone hypersensitivity.